Dynamics of Soft Matter Neutron Applications - GARCIA SAKAI, VICTORIA; Alba-Simionesco, Christiane; Chen, Sow Hsin (Neutron Scattering Applications and Techniques,, 2012)
Dynamics of Soft Matter: Neutron Applications provides an overview of neutron scattering techniques that measure temporal and spatial correlations simultaneously, at the microscopic and mesoscopic scale. Emphasizing the complementarities of scattering techniques with other spectroscopic ones, this volume also highlights the potential gain in combining with techniques such as rheology, NMR, light scattering, dielectric spectroscopy, as well as synchrotron radiation experiments. Key areas covered include polymer science,biological materials, complex fluids and surface science. Neutron scattering techniques offer answers to new questions arising at the interface of physics, chemistry,and biology. Knowledge of the dynamics at these levels is crucial to understanding the soft matter field, which includes colloids, polymers,membranes, biological macromolecules, foams, emulsions with applications towards biological and biomimetic systems, and phenomena involving wetting, friction,adhesion, or micro- and nano-fluidics. In summary, this book: Explores neutron scattering techniques to examine soft matter at the micro- and mesoscopic scales Examines soft matter, with a focus in polymer science, biological materials, complex fluids and surface science Discusses neutron scattering techniques combined with other spectroscopic methods Dynamics of Soft Matter Neutron Applications is an ideal book for scientists,engineers and advanced students seeking a reference on how neutrons are a key tool to study of the dynamical processes in soft materials.